Barriers to recovery‐focused care within therapeutic relationships in nursing: Attitudes and perceptions. (29th May 2019) - Harris, Barbara; Panozzo, Gina
Abstract: There are numerous barriers to the therapeutic relationship between nurses and persons with schizophrenia, such as time constraints, communication issues and the requirements of practice policies. The main point of this paper is that the nature of these barriers is such that the nurse may not conceptualize these as barriers or be aware of how his or her responses to these can further entrench existing barriers to relationship or create new ones. If the nurse is not aware of how he or she responds to time pressure, frustration or lack of clarity of practice policy and address this, there is a risk that the patient may perceive the nurse's actions as lacking in care, presence or involvement. As consumers increasingly embrace recovery approaches to mental health that prioritize therapeutic activities within the context of collaborative relationship, psychiatric nurses, with a long tradition of therapeutic relationship, can rise to meet them. It is suggested here that this can only occur if nurses are fully aware of barriers to relationship, their responses to these and the impact of these on relationship with patients. Suggestions for educational and empirical work to further raise awareness and promote understanding of this process are provided.